2014
DOI: 10.1007/s11033-013-2967-7
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to diethylhexyl phthalate (DEHP) results in a heritable modification of imprint genes DNA methylation in mouse oocytes

Abstract: Diethylhexyl phthalate (DEHP) is an estrogen-like compound widely used as a plasticizer in commercial products and is present in medical devices, and common household items. It is considered an endocrine disruptor since studies on experimental animals clearly show that exposure to DEHP can alter epigenetics of germ cells. This study was designed to assess the effects of DEHP on DNA methylation of imprinting genes in germ cells from fetal and adult mouse. Pregnant mice were treated with DEHP at doses of 0 and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(72 citation statements)
references
References 27 publications
1
68
2
1
Order By: Relevance
“…Hypomethylation of Tbx15 has previously been correlated with low birth weight, which is a risk factor for the development of obesity in adults (35). In the present study, DNA methylation of Tbx15 was not detected; however, a recent study has reported that gestational exposure to DEHP at 40 mg/kg may affect the DNA methylation of imprinting genes in fetal germ cells and growing oocytes, and in the offspring's oocytes (36). Therefore, it was inferred in the present study that the differential expression levels of Tbx15 mRNA in subcutaneous and visceral fat tissues between the control and DEHP groups may be due to an alteration in Tbx15 methylation status following in utero DEHP exposure.…”
Section: Dehp (Mg) --------------------------------------------------contrasting
confidence: 77%
“…Hypomethylation of Tbx15 has previously been correlated with low birth weight, which is a risk factor for the development of obesity in adults (35). In the present study, DNA methylation of Tbx15 was not detected; however, a recent study has reported that gestational exposure to DEHP at 40 mg/kg may affect the DNA methylation of imprinting genes in fetal germ cells and growing oocytes, and in the offspring's oocytes (36). Therefore, it was inferred in the present study that the differential expression levels of Tbx15 mRNA in subcutaneous and visceral fat tissues between the control and DEHP groups may be due to an alteration in Tbx15 methylation status following in utero DEHP exposure.…”
Section: Dehp (Mg) --------------------------------------------------contrasting
confidence: 77%
“…14,27 It has been demonstrated that glucuronidation is one of the detoxification mechanisms in the body and that the detoxification capacity of phthalates is decreased in case of low-grade glucuronidation. Authors found that there was low-grade glucuronidation in the autism spectrum disorder group.…”
Section: Discussionmentioning
confidence: 99%
“…[dibutil ftalat dibutyl phthalate (DBP)]'nin c-myc proto-onkogeninde hipometilasyona yol açarak cmyc'yi aktive ettiği bildirilmiştir. 88 90 Fetal testis DEHP'in ana hedefidir. DEHP'ye maternal maruziyetin fare testisinde DNA metilasyonunu ve DNA metiltransferaz ekspresyonunu artırdığı belirlenmiştir.…”
Section: R Re Ea Ak Kt Ti If F Ounclassified